Advanced machining processes of metallic materials : theory, modelling and applications - Grzesik, Wit (Elsevier, 2008)
This book brings updated knowledge on the metal cutting processes in relation to theory and industrial practice. In particular, many topics reflect recent developments, as for instance modern tool materials, computational machining, computer simulation of various process phenomena, chip control, monitoring of the cutting state, progressive and hybrid machining operations, and generation and modelling of surface integrity. This book addresses present state and future development of machining technologies. It provides a comprehensive description of metal cutting theory, experimental and modellin.